Participation motivation in disabled athletes - Bekir Furkan Tüzer; Havva Demirel (Physical Education of Students)
Background and Study Aim. Sports have significant effects on individuals of all ages and levels, particularly for those with disabilities. These effects are seen in terms of self-expression and competence skills. The aim of this study was to measure the motivation levels of disabled athletes in their participation in sports.